SEGMENTASI KONSUMEN COFFEE SHOP GENERASI Z DI JATINANGOR - Diana Rachmatunnissa; Yosini Deliana (Universitas Galuh Ciamis, 2020)
Coffee consumption rate in Indonesia has been increasing since 2013. This fact goes simultaneously with the increase of the number of coffee shops that was built in the last few years. Aside from being a place in which consumers can buy and consume coffee, these coffee shops also developed theirs facilities so that it can be a place for the consumers to socialize or as a comfortable place to do their works. Along with the development of the coffee shops’ facilities, there is also a development in the consumers’ mindset. In the last few years, generation Z has began to grow and became one of the targets of coffee shop consumer demographics. Jatinangor is an education area where a lot of students, who are included as generation Z, do most of their activities. The purpose of this study is to identify the characteristics of generation Z consumers and to identify the preferences of generation Z consumers towards coffee shops in Jatinangor. The sample selection in this study used systematic random sampling technique with a sample of 163 respondents. The analysis used was descriptive analysis and discriminant analysis. The results of this study showed the demography and psychography characteristics of generation Z consumers in a big coffee shop and a small coffee shop in Jatinangor and showed significant differences in variables such as age, consumption intensity, expense, number of visits, number of people, distance, traveling time, time spent at the coffee shop, and visiting time between the consumers.